2020
DOI: 10.2147/jep.s265620
|View full text |Cite
|
Sign up to set email alerts
|

<p>Experimental Carbonic Anhydrase Inhibitors for the Treatment of Hypoxic Tumors</p>

Abstract: Carbonic anhydrase (CA, EC 4.2.1.1) isoforms IX and XII are overexpressed in many hypoxic tumors as a consequence of the hypoxia inducible factor (HIF) activation cascade, being present in limited amounts in normal tissues. These enzymes together with many others are involved in the pH regulation and metabolism of hypoxic cancer cells, and were validated as antitumor targets recently. A multitude of targeting strategies against these enzymes have been proposed and are reviewed in this article. The small molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 143 publications
0
55
0
Order By: Relevance
“…All these studies confirmed the usefulness of this clinical candidate, SLC-0111, in tumours and other biomedical conditions. Although Jonsson and Liljas presumably read our reply 180 , in their reply to our reply they continue that they, “would have liked to see a properly reported inhibition study of this compound to make it obvious that it indeed is a good enough inhibitor to enter Phase I/Phase II studies” 181 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…All these studies confirmed the usefulness of this clinical candidate, SLC-0111, in tumours and other biomedical conditions. Although Jonsson and Liljas presumably read our reply 180 , in their reply to our reply they continue that they, “would have liked to see a properly reported inhibition study of this compound to make it obvious that it indeed is a good enough inhibitor to enter Phase I/Phase II studies” 181 .…”
Section: Discussionmentioning
confidence: 90%
“…We have replied to the technical issues raised by Jonsson and Liljas, as mentioned above. In their comment on our reply 180 they indicated they were “ happy by our prompt response ” and that some clarifications were achieved 181 , however now their criticism relating to the measurement of inhibition constants was extended to the entire medicinal chemistry community, not only to our group, stating that the “ original article was not intended to raise specific concerns regarding just one research group but rather was intended to raise concerns regarding medicinal chemistry publications in general, and we are glad that Prof. Supuran agrees that there is room for improvement! ” CTS hardly agrees with anything from their analysis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, many studies indicated that inhibiting this enzyme has a therapeutic effect on primary tumour and metastases growth [ 18 , 19 ]. These findings were relevant for the validation of CAIX as an anticancer therapeutic target [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sulphonamide derivatives acting as effective CAIX inhibitors showed significant anticancer activity in vitro and/or in vivo in many cell types and cancer models, with one such compound, SLC-0111, presently in Phase Ib/II clinical trials for the management of advanced, metastatic solid tumours [ 18 , 21 ]. Small-molecule CAIX inhibitors [ 21 ], but also small-molecule drug conjugates, antibody-drug conjugates, or cytokine-drug conjugates, targeting these enzymes were demonstrated to constitute an innovative antitumor strategy in the last decade [ 22 ]. In the present study, the cytotoxic effects of a sulphonamide CAIX inhibitor, derivative compound E (4-(2-((5-bromo-2-hydroxybenzyl) amino) ethyl) benzenesulphonamide), were investigated in the cancer cells with high CAIX expression.…”
Section: Introductionmentioning
confidence: 99%